Analysis of The Use of Village Funds In Economic Development (Case Study In Pa'bentengan Village, Ererasa District, Bantaeng Regency) - Rahman, Abdul (Pelopor Publikasi Akademika, 2023)
Utilization of Village Funds in Supporting Infrastructure Development in Pabentengang Village, Eremerasa District, Bantaeng Regency, thesis for the Development Economics study program, Faculty of Economics, Turatea Indonesia Institute Yapti Jeneponto. Supervised by Advisor I Profesor. Dokter. H. The intent of Juri, S. pd, S. E,. Meter. Meter and bos II by Dokter. H. Abdul Belas kasih,. S. pd,. S. E,. Meter. Meter Village funds are a government program in supporting village development, namely through village funds as a source of village income. As according to Law Number 6 of 2014 concerning villages, article 72 states that village funds are one source of village income sourced from the APBN. The purpose of this study was to determine the use of village funds in accordance with the program, the results of the use of village funds and community involvement in Pabentengan Village, Eremerasa District, Bantaeng Regency. The results of this study indicate that the use of Village Funds in Supporting the Infrastructure Development of Mamampang Village has been effective. This can be proven by the number of development programs that have been realized in accordance with the development plan. Community involvement in the use of village funds is also quite good, where the community has been involved in the preparation of bank plans up to the stage of the program development